Body mass scaling of projected frontal area in competitive cyclists - Heil, D. P. (European Journal of Applied Physiology, 2001)
The primary purpose of this study was to evaluate the scaling relationship between body mass (mb) and projected frontal area (AP) of competitive male cyclists whilst allowing statistically for the influence of bicycle geometry. A group of 21 cyclists [mean mb 74.4 (SD 7.2) kg, mean height 1.82 (SD 0.06) m, mean age 23.6 (SD 5.1) years] volunteered to have Ap determined from photographs at three trunk angles (TA: 5°, 15°, 25°) for each of three seat-tube angles (STA: 70°, 75°, 80°) using a modified cycle ergometer. Using multiple log-linear regression analysis procedures, the following equation was developed: Body Ap (meters squared)=0.00433×(STA0.172)×(TA0.0965)×(mb0.762) (r2=0.73, SEE=0.017 m2) (n=183 images total). This equation indicates that after allowing for the independent influence of STA and TA on Ap, Ap was proportional to mb raised to the +0.762 power (i.e. Ap\proptomb0.762). The 95% confidence interval for this exponent (0.670-0.854) barely included the theoretical two-thirds value but not the +0.55 value for Ap or the +0.32 value for submaximal metabolic power $$\dot W_{\rm s} $$) of outdoor cycling reported in the literature. Further analysis of wind tunnel data reported in the literature suggests that the coefficient of drag (CD) is proportional to mb raised to the -0.45 power. When combined with the present study findings, it is suggested that the drag area (CD×AP), which should be proportional to $$\dot W_{\rm s} $$ at submaximal cycling velocities, is proportional to mb to the +0.312 power (i.e. CD×Ap\propto(mb-0.45)×(mb+0.762)=mb+0.312), which is consistent with the +0.32 exponent for $$\dot W_{\rm s} $$ in the literature.